BOMBAX CEIBA LINN: A CRITICAL REVIEW ON PHYTOCHEMISTRY, TRADITIONAL USES, PHARMACOLOGY, AND TOXICITY FROM PHYTOPHARMACEUTICAL PERSPECTIVE - GUPTA, NIRAJ; SHARMA, DEVENDER; RANI, REKHA (International Journal of Pharmacy and Pharmaceutical Sciences, 2023)
Traditional medicines are becoming crucial and decisive role in the prevention and cure of diseases and disorders. Traditional medicines have various pharmacological activities which important for human health. Bombax Ceiba widely used from past decades for the treatment of diseases and disorders. Bombax ceiba is usually referred to as kapok tree and moca, which belongs to Bombacaceae. Moca is a crucial medicative, plant widely found in a tropical and subtropical Asian country like India, Pakistan. Various scientific studies or medicative usage has been reported within the traditional systems of drugs like Ayurveda, Siddha and Unani. Owing to this widespread attention about traditional medicines, scientific validations of medicinal plants have become a thrust area of research. In this paper, the scientific validation of Bombax ceiba for various biological activities has been reviewed with its chemical constituents present in the whole plant and with its traditional and contemporary uses. This manuscript also provides deep inside of recent patents associated with Bombax ceiba in the past decade.